La gestión de marketing y su incidencia en las ventas en la gelatería Altromix, sucursal Riobamba. - Paguay Valdiviezo, Cristin Nohemy (2024)
This research focuses on analyzing how marketing management influences the sales of the Altromix gelateria, located in Riobamba. The main objective is to propose marketing strategies that enhance the establishment's sales performance, addressing specific challenges in the local market. Using a hypothetical-deductive approach and a descriptive method, data were collected from customers, and interviews were conducted with the branch staff. To evaluate the study’s hypothesis, the Chi-Square test was applied, yielding a calculated value of 396.500, which significantly exceeds the tabulated value of 16. This led to the rejection of the null hypothesis and the confirmation of the research hypothesis, demonstrating that marketing management has a direct impact on Altromix's sales in Riobamba. This study concludes that effective marketing management not only improves current sales but also enables agile adaptation to market conditions and leverages growth opportunities. By better understanding customer needs and preferences, Altromix can develop more effective marketing strategies to increase customer satisfaction and strengthen brand loyalty.